2020
DOI: 10.1038/s41467-020-19144-7
|View full text |Cite
|
Sign up to set email alerts
|

Native mass spectrometry reveals the initial binding events of HIV-1 rev to RRE stem II RNA

Abstract: Nuclear export complexes composed of rev response element (RRE) ribonucleic acid (RNA) and multiple molecules of rev protein are promising targets for the development of therapeutic strategies against human immunodeficiency virus type 1 (HIV-1), but their assembly remains poorly understood. Using native mass spectrometry, we show here that rev initially binds to the upper stem of RRE IIB, from where it is relayed to binding sites that allow for rev dimerization. The newly discovered binding region implies init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…As electrostatic interactions between the peptides and oligonucleotides are strong enough to survive in the gas phase, , native top-down mass spectrometry of these complexes can be used to map the binding site. Complexes of HIV-1 TAR (transactivation responsive) RNA and a basic arginine-rich peptide (H 2 N-GRKK­RRQR­RRPP-NH 2 ) were studied by CID .…”
Section: Mass Spectrometry Studies Of Nucleic Acid Noncovalent Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…As electrostatic interactions between the peptides and oligonucleotides are strong enough to survive in the gas phase, , native top-down mass spectrometry of these complexes can be used to map the binding site. Complexes of HIV-1 TAR (transactivation responsive) RNA and a basic arginine-rich peptide (H 2 N-GRKK­RRQR­RRPP-NH 2 ) were studied by CID .…”
Section: Mass Spectrometry Studies Of Nucleic Acid Noncovalent Complexesmentioning
confidence: 99%
“…Time-dependent MS data showed 1:2 and 1:1 stoichiometries of TAR-tat complexes, shown in Figure . Native mass spectrometry revealed the binding stoichiometry and binding mechanism of RRE stem IIB RNA with rev ARM peptides . ESI-MS showed that stem IIB RNA formed complexes with one or two ARM peptides and full length RRE stem IIB RNA binds with one or five rev ARM peptides.…”
Section: Mass Spectrometry Studies Of Nucleic Acid Noncovalent Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Native mass spectrometry (MS) is a powerful biophysical technique for studying bio-macromolecular assemblies and their interactions with molecules. Under carefully tuned conditions, native MS preserves noncovalent interactions in the gas phase , and provides insight into individual ligand binding events and binding stoichiometry. For this reason, native MS can be utilized to elucidate the interactions between biomolecules and small molecules, such as for proteins interacting with lipids, drugs, nucleotides, and peptides. Native MS has also advanced to determine binding constants and thermodynamics of protein–lipid interactions and allostery between protein–lipid interactions and small molecules, such as other lipids, , and drugs. , …”
Section: Introductionmentioning
confidence: 99%
“…The use of MS/MS for structural interrogation of oligonucleotidecontaining complexes has emerged as useful for a few studies focused on ligand localization and conformational changes. 22,26,28,31,34,45 However, in the case of non-covalent complexes, collisional activation methods, although providing some sequence information, do not afford extensive information related to ligand localization and overall complex structure. To combat these decits, alternative activation methods that are more suitable for the analysis of non-covalent macromolecular complexes have been developed, including surfaceinduced dissociation (SID), 46 electron activation methods, 47 and ultraviolet photodissociation (UVPD).…”
Section: Introductionmentioning
confidence: 99%